First report of detection of Canine Parvovirus type 2 in naturally infected domestic cats in Egypt by duplex PCR for simultaneous detection of Canine Parvovirus type 2 and Feline Panleukopenia virus - Magouz, AF; Elkon, I; Khaled, E; Alkhalefa, N (Journal of the Hellenic Veterinary Medical Society, 2023)
Feline Panleukopenia virus (FPLV) and Canine Parvovirus type 2 (CPV) cause fatal gastroenteritis in cats and dogs. In this study we developed a duplex polymerase chain reaction (dPCR) assay for the concurrent detection of FPLV and CPV-2 in a single PCR tube. Two primers were used based on nucleic acid conserved regions of the two viruses which specifically amplify 237 bp of the VP2 gene of FPLV and 583 bp of the VP2 gene of CPV 2.Sensitivity and Specificity of the dPCR were evaluated. A total of 30 rectal/fecal swabs were collected from domestic cats in Kafrelsheikh province, Egypt and were tested for FPLV and CPV-2 viruses using the dPCR assay. The results revealed that this dPCR assay was sensitive, as it could detect a minimum of 1 × 105 copies of genomic DNA of the two viruses. The dPCR assay was highly specific as there was no amplification of nucleic acid of other feline and canine pathogens. The positive ratio was 83.3% (25/30) for FPLV and 16.6% (5/30) for CPV respectively. Further analyses of CPV samples by Restriction Fragment Length Polymorphism (RFLP) revealed that they are classified as CPV 2a/2b variants. This study reports the first detection of CPV 2a/2b from symptomatic cats in Egypt using dPCR assay that can detect FPLV and CPV in a single tube reaction.